2022
DOI: 10.3390/ijerph19158910
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Decoupling between Net Carbon Emissions and Construction Land and Its Driving Factors: Evidence from Shandong Province, China

Abstract: Human activities and land transformation are important factors in the growth of carbon emissions. In recent years, construction land for urban use in China has expanded rapidly. At the same time, carbon emissions in China are among the highest in the world. However, little is known about the relationship between the two factors. This study seeks to estimate the carbon emissions and carbon sequestrations of various types of land based on the land cover data of 137 county-level administrative regions in Shandong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 80 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…The increase in information entropy of land use structure reflects that the types and proportions of land use become more complex within a certain geographical space, and the findings of this study show that a more chaotic land-use structure leads to an increase in carbon emissions. Some researchers are concerned that the decrease in forest land will weaken the carbon sink capacity of the environment, and the expansion of construction land will lead to the increase in carbon sources [ 44 , 45 ]. Meanwhile, Liu’s (2016) research demonstrates that soil change influences the carbon sink capacity [ 46 ], and the Sichuan basin has experienced rapid urbanization and quick changes in land use structure in the last 20 years, indicating the trend of rapid urban expansion and hence increased carbon emissions.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in information entropy of land use structure reflects that the types and proportions of land use become more complex within a certain geographical space, and the findings of this study show that a more chaotic land-use structure leads to an increase in carbon emissions. Some researchers are concerned that the decrease in forest land will weaken the carbon sink capacity of the environment, and the expansion of construction land will lead to the increase in carbon sources [ 44 , 45 ]. Meanwhile, Liu’s (2016) research demonstrates that soil change influences the carbon sink capacity [ 46 ], and the Sichuan basin has experienced rapid urbanization and quick changes in land use structure in the last 20 years, indicating the trend of rapid urban expansion and hence increased carbon emissions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the carbon sink coefficients were set across different land use types, without consideration of the difference of the carbon sink intensity within the same land use types with different vegetation composition [34]. In fact, it is notable that the carbon sink coefficients of the same land use type may vary greatly in different regions, and it is necessary to carry out relevant research on the carbon sink coefficients according to the specific conditions of different regions [38]. Meanwhile, this study also ignored the variations in the carbon sink per unit land area across time, which can generally remain approximately stable during a long-term period but may vary greatly in a short-term period during some short-term disturbances, e.g., extreme climate change [39].…”
Section: Discussionmentioning
confidence: 99%
“…With increasing attention on carbon emissions and land use patterns and quality in China, Li et al (2022) used land cover data from 137 county-level administrative units in Shandong Province from 2000 to 2020 to estimate the carbon emissions and carbon sequestration of different land types. They found that land use intensity and technological innovation efficiency restrained carbon emissions, and the relationship between net carbon emissions and construction land evolved from an expansive negative decoupling type to a strong negative decoupling type [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The development of regional socio-economics and urbanization has accelerated the expansion of construction land globally, with some areas even experiencing unregulated expansion [8]. The expansion of construction land increases direct carbon emissions and occupies a large amount of vegetation-covered ecological land, weakening the surface carbon sink capacity and carbon sequestration [9]. Additionally, due to the different use purposes, usage methods, and intensities of various types of construction land, the corresponding energy consumption demands also vary [10].…”
Section: Introductionmentioning
confidence: 99%